Outcome measures for Takayasu's arteritis - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2015)
Purpose of reviewTakayasu's arteritis (TAK) is a large-vessel vasculitis with a chronic, indolent course affecting the aorta and its main branches. This review will describe the recent studies to develop validated outcome measures to assess TAK.Recent findingsTAK is traditionally assessed with a physician's global assessment including symptoms and signs of inflammation and vascular insufficiency, acute-phase reactants (APRs), and imaging including conventional digital subtraction angiography, computerized tomographic, and magnetic resonance angiography, and recently 18-FDG-PET. Recent attempts to develop a validated tool for disease assessment include the Indian Takayasu Clinical Activity Score (ITAS2010), which incorporates clinical signs and symptoms with APRs in a simplified and weighted adoption of the Birmingham Vasculitis Activity Score. Among biomarkers to assess clinical activity, pentraxin-3 is perhaps the most promising, but its validity and superiority against APRs in clinical practice need to be demonstrated. Patient-reported outcomes (PROs) are increasingly recognized as of substantial importance to measure in clinical trials

in addition to so-called generic' tools such as the SF-36 or measures of fatigue, disease-specific instruments would likely help capture aspects of TAK not measured by generic quality-of-life assessments or physician-based tools.SummaryAlthough outcome measures for TAK are not sufficiently validated, progress in the assessment of TAK is reflected in recent studies with new tools such as ITAS2010, new biomarkers, and a variety of PROs.
Keywords: disease assessment; outcome measures; Takayasu's arteritis; QUALITY-OF-LIFE; LARGE-VESSEL VASCULITIS; DISEASE-ACTIVITY; CLINICAL-TRIALS; DIAGNOSIS; MANAGEMENT; EFFICACY; HEALTH; INTERVENTION; PROGRESSION